2020
DOI: 10.1507/endocrj.ej19-0379
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy and limitations of potassium iodide for patients newly diagnosed with Graves’ disease

Abstract: The efficacy of potassium iodide (KI) for Graves' disease (GD) has been reported, although few clinical reports have examined the long-term efficacy of treatment. The objective of this study was to investigate the efficacy and limitations of KI treatment for GD. This study enrolled patients newly diagnosed with mild GD, defined as free thyroxine (FT4) <5.0 ng/dL, between July 2014 and June 2016. KI was started at a dose of 50 mg/day, and if FT4 values did not decrease after initiation of treatment, doses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Okamura et al 20 showed that KI monotherapy was effective in 65.9% of patients with thionamide-associated side effects, with 38.6% of the patients experiencing remission after KI therapy. Suzuki et al 21 reported that KI therapy was effective and safe in almost 60% of patients with mild GD, which was defined as an FT4 level <5.0 ng/dL. Furthermore, they suggested that an FT4 cut-off of 2.76 ng/dL was optimal for differentiating between responders and non-responders 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okamura et al 20 showed that KI monotherapy was effective in 65.9% of patients with thionamide-associated side effects, with 38.6% of the patients experiencing remission after KI therapy. Suzuki et al 21 reported that KI therapy was effective and safe in almost 60% of patients with mild GD, which was defined as an FT4 level <5.0 ng/dL. Furthermore, they suggested that an FT4 cut-off of 2.76 ng/dL was optimal for differentiating between responders and non-responders 21.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al 21 reported that KI therapy was effective and safe in almost 60% of patients with mild GD, which was defined as an FT4 level <5.0 ng/dL. Furthermore, they suggested that an FT4 cut-off of 2.76 ng/dL was optimal for differentiating between responders and non-responders 21. Based on these findings, we chose KI monotherapy as the initial treatment in our case, as the negativity of TRAb indicated a milder clinical course and less severe side effects were preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Serum antithyroglobulin antibody (TgAb) and antithyroid peroxidase antibody (TPOAb) levels were determined by ECLIA using an ECLusys Anti-Tg and Anti-TPO kit (Roche Diagnostics). Serum TRAb levels were determined by ECLIA using an ECLusys TRAb electrochemiluminescence immunoassay kit (Roche Diagnostics) [ 18 ]. Serum TSAb levels were measured using a TSAb radioimmunoassay and bioassay kit (Yamasa, Choshi, Japan).…”
Section: Case Presentationmentioning
confidence: 99%
“…Basically, antithyroid drugs (ATDs) were initiated for patients with hyperthyroidism. Potassium iodide was administrated in combination with ATDs for patients with severe Graves' disease [21] and as monotherapy for patients with mild Graves' disease [22]. Assessments at 3, 6, 9, and 12 months included FT 4 , FT 3 , TSH, BNP, and hsTnI.…”
Section: Patient Selection and Clinical Recordsmentioning
confidence: 99%